The Influence of Mathematical Literacy Ability and Critical Thinking Ability on Mathematical Problem Solving Ability - Almas Adlina; Edy Syahputra; Pardomuan Sitompul (Study Program of Mathematics Education of Unimed Postgraduate Program, 2024)
The aims of this research are: (1) To find out how mathematical literacy skills and critical thinking skills affect mathematical problem solving abilities simultaneously, (2) to find out how mathematical literacy skills and critical thinking skills affect mathematical problem solving abilities. part. This study used a quantitative research approach. This research was carried out at SMPS Bina Taruna Medan, SMPN 20 Medan and SMPN 33 Medan. The subjects of this research were students in class VII-1 in three schools totaling 90 students. The sampling method in this study was a random sampling technique. The instruments used consisted of: (1) a test of mathematical literacy skills, (2) a test of critical thinking skills, (3) a test of mathematical problem solving abilities. Data analysis was performed using multiple linear regression analysis. The results of the research show: (1) There is an influence of mathematical literacy skills and critical thinking skills on mathematical problem solving abilities simultaneously, (2) There is an influence of mathematical literacy skills and critical thinking skills on mathematical problem solving abilities. partial capability. (3) mathematical literacy skills and critical thinking skills have an influence of 90.1% on simultaneous mathematical problem solving abilities, while 9.9% is determined by other variables.